µ-Crystallin: A thyroid hormone binding protein - Kinney Christian J. (Sciendo, 2021)
µ-Crystallin is a NADPH-regulated thyroid hormone binding protein encoded by the CRYM gene in humans. It is primarily expressed in the brain, muscle, prostate, and kidney, where it binds thyroid hormones, which regulate metabolism and thermogenesis. It also acts as a ketimine reductase in the lysine degradation pathway when it is not bound to thyroid hormone. Mutations in CRYM can result in non-syndromic deafness, while its aberrant expression, predominantly in the brain but also in other tissues, has been associated with psychiatric, neuromuscular, and inflammatory diseases. CRYM expression is highly variable in human skeletal muscle, with 15% of individuals expressing ≥13 fold more CRYM mRNA than the median level. Ablation of the Crym gene in murine models results in the hypertrophy of fast twitch muscle fibers and an increase in fat mass of mice fed a high fat diet. Overexpression of Crym in mice causes a shift in energy utilization away from glycolysis towards an increase in the catabolism of fat via β-oxidation, with commensurate changes of metabolically involved transcripts and proteins. The history, attributes, functions, and diseases associated with CRYM, an important modulator of metabolism, are reviewed.